Pattern of Sharia Compliance In KSPPS In Pekalongan City (Analysis of Constraints And Solutions To The Deed of Financing) - Tarmidzi, Tarmidzi; Inayati, Anindya Aryu; Mulyawisdawati, Richa Angkita; Yaqin, Alamul (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
This research aims to find out, how is Sharia Compliance KSPPS in Pekalongan City, and the factors causing it in Pekalongan City? The method and approach in this study is a qualitative approach. The qualitative approach is an approach method by capturing social phenomena in the community to be further described in the form of a narrative by revealing the results of the arrests as they are. The results of this research are as follows: first; Sharia compliance discusses the entire process starting from socialization, distribution or application to completion of settlement, in general it has implemented compliance in accordance with sharia principles, although some aspects have not been met. Second; There are patterns of sharia non-compliance from a number of instruments in financing at KSPPS based on three patterns of influence, a) educational perspective: DPS at KSPPS in Pekalongan City still do not have a DPS certificate, customers or members who do not understand and understand clearly related to contracts in sharia financing, managers who do not have an understanding of sharia (muamalah). b) rational perspective: conventional banking facilities and technology are more sophisticated when compared to Islamic banks, the non-applicability of reporting systems and profit sharing in accordance with Islamic principles and Islamic accounting, because they are considered too complicated and difficult for customers. c) the emotional perspective of Muslims who make choices in KSPPS for religious reasons is still small compared to rationality reasons, so they choose conventional banks.